Alat Etsa Printed Board Circuit (PCB) Otomatis Dengan ESP32-CAM Dan Pemantauan Berbasis Telegram - Aufi, Nizarruddien Al; Anshory, Izza; Jamaaludddin, Jamaaluddin; Falah, Agus Hayatal (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2025)
The development of technology has a tremendous impact on human life. Work that previously required many large devices and was done manually, then with the development of technology, the work only requires a small tool and can work automatically, namely a microcontroller. The use of microcontrollers is very influential in the development of technology, many new tools have been created which are updates from previous tools, one of which is the process of making Printed Board Circuit (PCB) paths or also called the etching process. The etching process is carried out manually by immersing the PCB in FeCL3 liquid and then moving it manually for a few minutes, this is inefficient and can endanger users if it comes into contact with their hands. This study aims to develop the etching process so that it can work automatically and users can see the process through the Telegram application on their Smartphone. There are several factors why ESP32 - Cam is chosen as a microcontroller, including the camera feature that allows users to monitor directly in different places, besides that the ports are quite numerous and easy to connect to the telegram application